The Changing Landscape of Systemic Treatment for Cervical Cancer: Rationale for Inhibition of the TGF-β and PD-L1 Pathways - Birrer, Michael J.; Fujiwara, Keiichi; Oaknin, Ana; Randall, Leslie; Ojalvo, Laureen S.; Valencia, Christian; Ray-Coquard, Isabelle (Frontiers in Oncology, 2022)
Cervical cancer is one of the most common and lethal cancers among women worldwide. Treatment options are limited in patients with persistent, recurrent, or metastatic cervical cancer, with <20% of women living >5 years. Persistent human papillomavirus (HPV) infection has been implicated in almost all cases of cervical cancer. HPV infection not only causes normal cervical cells to transform into cancer cells, but also creates an immunosuppressive environment for cancer cells to evade the immune system. Recent clinical trials of drugs targeting the PD-(L)1 pathway have demonstrated improvement in overall survival in patients with cervical cancer, but only 20% to 30% of patients show overall survival benefit beyond 2 years, and resistance to these treatments remains common. Therefore, novel treatment strategies targeting HPV infection–associated factors are currently being evaluated in clinical trials. Bintrafusp alfa is a first-in-class bifunctional fusion protein composed of the extracellular domain of the TGF-βRII receptor (a TGF-β “trap”) fused to a human immunoglobulin G1 monoclonal antibody that blocks PD-L1. Early clinical trials of bintrafusp alfa have shown promising results in patients with advanced cervical cancer.